The Influence of Self-Control, Social Pressure, and Promotional Strategies on the Consumer Behavior on Pay Later Consumer Behavior with Financial Literacy as a Moderation - Juphiter Henry; Sellyna Sellyna; Belicia Anabel; Randy Kuswanto (LPPM Universitas Buddhi Dharma, 2026)
The rapid development of financial technology has led to a significant increase in the use of pay-later services, in Indonesia, offering transactional convenience but also raising concerns over rising consumerist behavior. This study aims to analyze the influence of self-control, social pressure, and promotional strategies on the consumptive behavior of pay later users, with financial literacy serving as a moderating variable. A quantitative research approach was employed, using questionnaires distributed to active pay later users in West Jakarta. Data were analyzed using multiple linear regression and moderated regression analysis (MRA). The findings are expected to demonstrate that self-control negatively affects consumptive behavior, while social pressure and promotional strategies have a positive influence. Furthermore, financial literacy is predicted to moderate these relationships by weakening both the negative and positive effects. The study provides theoretical and practical insights into understanding consumer behavior in digital finance, emphasizing the importance of financial literacy in promoting responsible spending.